Non-destructive methods for predicting sawn lumber properties from young, standing Eucalyptus grandis and Eucalyptus grandis X urophylla trees. - Prins, Ashlee Cherice (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScFor)--Stellenbosch University, 2021.